Extending the Planning Poker Method to Estimate the Development Effort of Parallel Applications - Andrade, Gabriella; Griebler, Dalvan; Santos, Rodrigo; Fernandes, Luiz Gustavo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2023: Anais do XXIV Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2023.235925, 2023)
Since different Parallel Programming Interfaces (PPIs) are available to programmers, evaluating them to identify the most suitable PPI also became necessary. Recently, in addition to the performance of PPIs, developers’ productivity has also been evaluated by researchers in parallel processing. Some researchers conduct empirical studies involving people for productivity evaluation, which is time-consuming. Aiming to propose a less costly method for evaluating the development effort of parallel applications, we proposed modifying the Planning Poker method in this paper. We consider a representative set of parallel stream processing applications to evaluate the proposed modification. Our results showed that the proposed method required less effort for practical use than the controlled experiments with students.